Green brands purchasing decisions among varying income groups in South Africa - Ramsunder, Kirana (My University, 2021)
Increasing consumer demand for products and services has put increasing pressure on the limited environmental resources, leading to the global growth of green products. In South Africa the research area of green consumer choices is new territory, with limited studies of scale currently available. The South African consumer is unique and whilst a few similar studies have been conducted in other emerging market countries, the academic body of research of scale in South Africa on green consumerism is sparse. Considering that consumption is impacting climate change and contributing to environmental degradation, finding sustainable solutions through daily consumption decisions is important. This study examined the impact of life values on willingness to purchase green products. It also tested the moderating effects of product categories, price of green products, brand loyalty and socio-economic level in the relationship between life values and willingness to purchase green products. Secondary quantitative data was used via the TGI Ask Afrika group to generate the results of this study with approximately 23346 datapoints and the analysis method of correspondence maps and cross tabulations. The five key hypothesis developed yielded positive relationships. TGI data presents consumer profiles in terms of consumer life value statements whereby psychographic and demographic data and key lifestyle statements are combined. The key contributions of this study establish a relationship with green food choices and brand loyalty, income groups and the overarching consumer life values. These findings further the body of South African research and contribute to the green marketing territory, in alignment with similar studies conducted in other emerging markets
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Strategic Marketing, 2021
Keywords: Green Purchasing Decision; Willingness to purchase; Green Product; Willingness to pay more; Socio-Economic levels; Household income; Life values; SDG-8: Decent work and economic growth